Application development in process firms: adding value to customer products and production systems. (21st May 2013) - Lager, Thomas; Storm, Per; Lager, Thomas; Blanco, Sylvie
<x xml:space="preserve">Abstract</x> The process industries span several industrial sectors such as minerals and metals, pulp and paper, food and beverages, chemicals and petrochemicals, utilities and generic pharmaceuticals, and thus constitute a considerable part of all manufacturing industry. Application development, as an institutionalised function in process industry firms, focuses on bridging the gap between a product supplier's knowledge of the product's performance scope and the customer's knowledge of its own production process requirements. In an exploratory survey of major process firms in the Swedish process industries, the importance of application development to firms was judged to be very high, but there also seemed to be a window of opportunity for improvements. The most important driver was 'an opportunity to establish long‐term sustainable customer relationships and to secure future product sales'. Expected customer outcomes differed substantially between firms. As extremes, one firm expected 80% of application development to give the customers improved products, while the other extreme expected only improved customer process technology. Because most of the firms in the study population had customers on a global market, it is argued that the research findings may be relevant and of value also to the larger worldwide population of interest.